2016
DOI: 10.1016/j.rser.2015.12.280
|View full text |Cite
|
Sign up to set email alerts
|

Trade liberalization, FDI inflows, environmental quality and economic growth: A comparative analysis between Tunisia and Morocco

Abstract: The aim of this research is to investigate the economic impacts of the trade liberalization on the environmental quality in Tunisia and Morocco. Specifically, the paper inspects whether liberalization of the trade sector has harmed the quality of the environment in both countries. To this end, we conduct various econometric models: a VECM and cointegration techniques for single country case study and a Panel VECM and Panel cointegration when using data of both country as a group. We also include a dummy variab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
59
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(71 citation statements)
references
References 78 publications
11
59
1
Order By: Relevance
“…Finally, trade changes the economic structure of the host country under the composition effect. This finding corroborates the works of Grossman and Krueger (1991), Menyah et al (2014), Falvey et al (2013), and Hakimi and Hamdi (2016).…”
Section: A Results Of the Total Samplesupporting
confidence: 92%
“…Finally, trade changes the economic structure of the host country under the composition effect. This finding corroborates the works of Grossman and Krueger (1991), Menyah et al (2014), Falvey et al (2013), and Hakimi and Hamdi (2016).…”
Section: A Results Of the Total Samplesupporting
confidence: 92%
“…While GDP showedno significant link with environmental degradation in long run as well as in short-run. The findings of the study werealigned with Grossman and Krueger [11], and Hakimi and Hamdi [6]. Furthermore, the error correction term wastelling 20% speed of adjustment in each year.…”
Section: Empirical Findingssupporting
confidence: 64%
“…As a result, the use of energy increased drastically, pollutant emissions surged and the environmental quality degenerated. All these factors have augmented the susceptibility of the ecosystem specifically in developing countries [6].…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the Granger causality analysis, they reported a unidirectional causality from energy consumption, trade openness and economic growth to CO 2 emissions and from trade openness to energy consumption and economic growth. Hakimi and Hamdi [26] probed the determinants of CO 2 emissions in Tunisia and Morocco during 1971-2013. They found that FDI, trade openness and capital positively affected CO 2 emissions in both countries' time series and panel analyses.…”
Section: Literature Reviewmentioning
confidence: 99%